Ketamine promptly normalizes excess norepinephrine and enhances dopamine neuronal activity in Wistar Kyoto rats - Daniels, Stephen; El Mansari, Mostafa; Hamoudeh, Rami; Blier, Pierre (Frontiers in Pharmacology, 2023)
Ketamine acts primarily by blocking the N-methyl-D-aspartate (NMDA) receptor at the phencyclidine site. The rapid antidepressant properties of ketamine were demonstrated in the clinic and several behavioral models of depression in rodents. We hypothesized that the normalization of abnormal activity of monoamine neurons in Wistar Kyoto (WKY) rats contributes to the rapid antidepressant effects of ketamine. A single administration of ketamine (10 mg/kg, i. p) or saline was administered to anesthetized WKY rats before in vivo electrophysiological recordings of dorsal raphe nucleus (DRN) serotonin (5-HT), locus coeruleus (LC) norepinephrine (NE) and ventral tegmental area (VTA) dopamine (DA) neuronal activity. Pyramidal neurons from the medial prefrontal cortex (mPFC) were also recorded before and after a ketamine injection. In the VTA, ketamine elicited a significant increase in the population activity of DA neurons. This enhancement was consistent with findings in other depression-like models in which such a decreased population activity was observed. In the LC, ketamine normalized increased NE neuron burst activity found in WKY rats. In the DRN, ketamine did not significantly reverse 5-HT neuronal activity in WKY rats, which is dampened compared to Wistar rats. Ketamine did not significantly alter the neuronal activity of mPFC pyramidal neurons. These findings demonstrate that ketamine normalized NE neuronal activity and enhanced DA neuronal activity in WKY rats, which may contribute to its rapid antidepressant effect.